A finite element model of the embryonic zebrafish heart electrophysiology. (February 2023) - Cestariolo, Ludovica; Luraghi, Giulia; L'Eplattenier, Pierre; Rodriguez Matas, Jose Felix
Highlights: Development of a full 3D model of the zebrafish heart electrophysiology. Model able to replicate the principal features of the zebrafish electrophysiology. Activation sequence and ECGs in line with experimental reported data. Abstract: Background and objective: In the last 30 years, a growing interest has involved the study of zebrafish thanks to its physiological characteristics similar to those of humans. The aim of the following work is to create an electrophysiological computational model of the zebrafish heart and lay the foundation for the development of an in-silico model of the zebrafish heart that will allow to study the correlation between pathologies and drug administration with the main electrophysiological parameters as the ECG signal. Methods: The model considers a whole body and the two chambers of three days post fertilization (3 dpf) zebrafish. A four-variable phenomenological action potential model describes the action potential of different heart regions. Tissue conductivity was calibrated to reproduce the experimentally described activation sequence. Results: The model is able to correctly reproduce the activation sequence and times found in literature, with activation of the atrium and ventricle that correspond to 36 and 59 ms, respectively, and a delay of 14 ms caused by the presence of the atrioventricular band (AV band). Moreover, the obtained in-silico ECG reflects the main characteristics of the zebrafish ECG in good agreement with experimental records, a P-wave with a duration of approximately the total atrial activation, followed by a QRS complex of approximately 109 ms corresponding to ventricle activation. Conclusions: The model allows the assessment of the main electrophysiological parameters in terms of activation sequence and timing, reproducing monopolar and bipolar ECG signals in line with experimental data. Coupling the proposed model with an electrophysiological detailed action potential model of zebrafish will represent a significant breakthrough toward the development of an in-silico zebrafish heart.